2018
DOI: 10.1002/elan.201800189
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐nanotube Modified Screen‐printed Electrode for the Simultaneous Determination of Nitrite and Uric Acid in Biological Fluids Using Batch‐injection Amperometric Detection

Abstract: A portable electroanalytical system applied for rapid and simultaneous determination of uric acid (UA) and nitrite (NIT) in human biological fluids (urine, saliva and blood) is reported. The system is based on batch‐injection analysis with multiple‐pulse amperometric (BIA‐MPA) detection using screen‐printed electrodes (SPEs) modified with multi‐walled carbon nanotubes. Sample dilution in optimized electrolyte (0.1 mol L−1 Britton‐Robinson buffer pH 2) followed by injection of 100 μL on the electrode surface us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 71 publications
0
15
0
1
Order By: Relevance
“…Polyester SPGE 0.06 0.08 0.05 4 [29] Pb 2 + Cu 2 + Hg(II) Biodiesel AuSPE 0.005 0.008 0.003 30 [82] Ciprofloxacin PF SPE modified with MWCNT 0.06 130 [83] Sildenafil PF SPE modified with GR 0.05 115 [84] Hg 2 + Biodiesel AuSPE 0.02 NR [85] Pb 2 + Aviation Fuel AuSPE 0.004 NR [86] Omeprazole PF SPE modified with MWCNT 0.009 120 [87] Corrosion inhibitors Ethanol, seawater and mineral oil SPGE 0.3 180 [88] Levamisole Levothyroxine PF SPCE or SPE modified with MWCNT Organic-resistant SPGE 0.14 0.10 170 150 [89] Nitrite Uric Acid Saliva, urine, and blood SPE modified with MWCNT 0.06 0.05 160 [90] Antioxidant capacity (DPPH) Edible oil Polyester SPGE 1.0 180 [91] [a] AF: analytical frequency (injections h À 1 ); LOD: limit of detection; PF: pharmaceutical formulation; PB: Prussian blue; GR: graphene; WE: working electrode. and selectivity) combine more with the characteristics of BIA systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyester SPGE 0.06 0.08 0.05 4 [29] Pb 2 + Cu 2 + Hg(II) Biodiesel AuSPE 0.005 0.008 0.003 30 [82] Ciprofloxacin PF SPE modified with MWCNT 0.06 130 [83] Sildenafil PF SPE modified with GR 0.05 115 [84] Hg 2 + Biodiesel AuSPE 0.02 NR [85] Pb 2 + Aviation Fuel AuSPE 0.004 NR [86] Omeprazole PF SPE modified with MWCNT 0.009 120 [87] Corrosion inhibitors Ethanol, seawater and mineral oil SPGE 0.3 180 [88] Levamisole Levothyroxine PF SPCE or SPE modified with MWCNT Organic-resistant SPGE 0.14 0.10 170 150 [89] Nitrite Uric Acid Saliva, urine, and blood SPE modified with MWCNT 0.06 0.05 160 [90] Antioxidant capacity (DPPH) Edible oil Polyester SPGE 1.0 180 [91] [a] AF: analytical frequency (injections h À 1 ); LOD: limit of detection; PF: pharmaceutical formulation; PB: Prussian blue; GR: graphene; WE: working electrode. and selectivity) combine more with the characteristics of BIA systems.…”
Section: Discussionmentioning
confidence: 99%
“…The attractive features of the BIASPE system were also explored for the on-site determination of carbendazim, catechol and hydroquinone in tap water, [20] metals (Zn 2 + , Cd 2 + , Pb 2 + , Cu 2 + , and Hg 2 + ) in biodiesel samples, [85] glucose in artificial serum sample, [21] antioxidant 2,6-di-tert-butylphenol (2, in biodiesel and jet-fuel using hydro-organic media as the supporting electrolyte, [26] lead in aviation fuel samples, [86] omeprazole in pharmaceutical samples, [87] corrosion inhibitors (2,5-dimercapto-1,3,5-thiadiazole) in fuel ethanol, seawater and mineral oil samples, [88] levamisole and sodium levothyroxine in pharmaceutical samples, [89] nitrite and uric acid in biological fluids (urine, plasma, saliva, and serum), [90] antioxidant capacity of edible oil samples, [91] benzocaine and tricaine in fish fillets, [92] and a robust electroanalytical system for detection of UVinduced DNA degradation. [93] Recently, Mendonça et al [94] reported a low-cost mechanized system fabricated using fused deposition modelling 3D-printing technology to perform injections on an electrochemical cell in wall-jet configuration (similar to a common BIA cell).…”
Section: -Nitro-p-phenylenediaminementioning
confidence: 99%
“…Fonte: Quintino, 2003(QUINTINO, 2003. Dentre as amostras biológicas, destaca-se a aplicação a análise de fluidos biológicos (CAETANO et al, 2018), como sangue, plasma, urina e saliva, onde marcadores são determinados, incluindo a dopamina. Alguns fatores podem interferir na análise eletroquímica de DP, como exemplo, a interferência de outros compostos em amostras biológicas, tais como ácido úrico e ácido ascórbico, e que possuem potencial de oxidação eletroquímica próximos ao potencial da dopamina; (SAJID et al, 2016) Foi reportado por Popa e colaboradores a detecção eletroquímica de dopamina na presença de ácido ascórbico utilizando como eletrodos filmes finos condutivos de diamante.…”
Section: Sistemas Portáteisunclassified
“…Inorganic nitrate in the organism are formed by Nitrate-Nitrite-Nitric Oxide pathway, and is an important metabolite and its variations can indicate numerous diseases, such as obesity (CAETANO et al, 2018). This component can act as a modulator of heart diseases or metabolite dysfunction (BRYAN et al, 2005;MONTI et al, 2003;ROBERTS et al, 2015).…”
Section: Detection Of Nit and Uamentioning
confidence: 99%
“…This component can act as a modulator of heart diseases or metabolite dysfunction (BRYAN et al, 2005;MONTI et al, 2003;ROBERTS et al, 2015). Its electroactivity is evidenced and there are several methods of detecting nitrite using electrochemical sensors (CAETANO et al, 2018;HU et al, 2012;METTERS;KADARA;BANKS, 2012).…”
Section: Detection Of Nit and Uamentioning
confidence: 99%